Electrolyte, lithium ion battery and electric device
By using the coordinated combination of lithium difluoroxalate borate, propyl trifluorocarbonate and fluoroforming additives in the lithium-ion battery electrolyte, the problem of volume expansion and low conductivity of silicon-based anode materials during charging and discharging is solved, and the cycling performance and high temperature stability of the battery are significantly improved.
Patent Information
- Application Number
- CN202411982098.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-30
AI Technical Summary
In traditional lithium-ion batteries, the silicon-based anode materials have problems such as severe volume expansion, low conductivity, short cycle life and low Coulomb efficiency during charging and discharging, which limits their commercial applications.
An electrolyte is adopted, including a non-aqueous organic solvent, lithium salt and specific additives, including lithium difluorooxalate borate, propylene trifluorocarbonate and fluoroforming additives. By collaborating and controlling their content proportional relationship, the solvation structure of the electrolyte is improved, and the stability of the positive and negative electrodes and the battery circulation performance are improved.
It effectively improves the stability of the electrolyte and the circulating performance of the battery, reduces the problems of circulating expansion and poor high temperature stability, and improves the overall performance of the battery.
Smart Images

Figure BDA0005221779170000021 
Figure BDA0005221779170000022 
Figure BDA0005221779170000041
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of secondary batteries, and in particular relates to an electrolyte, a lithium ion battery and an electrical device. Background Art
[0002] As a highly efficient energy storage device, the development of lithium-ion batteries has received widespread attention. With the advancement of technology and the increase in application needs, traditional lithium-ion batteries have gradually failed to meet the market's demand for higher energy density, faster charging speed and safer performance. In this context, silicon-based anode materials are regarded as strong candidates for the next generation of lithium-ion battery anode materials due to their high theoretical specific capacity. However, silicon-based anode materials have severe volume expansion, low electrical conductivity, short cycle life, and low coulombic efficiency during the charging and discharging process, which limit their commercial application.
[0003] In order to solve these problems, researchers have carried out a lot of work, including the structural design and modification of silicon-based materials, the development of new binders and electrolyte additives. Through these methods, the volume expansion of silicon-based materials can be suppressed to a certain extent, and their electrical conductivity and cycle stability can be improved. For example, by introducing a metal oxide coating layer on the surface of silicon-based negative electrode materials, such as amorphous TiO2 coating, the volume expansion of silicon during the charging and discharging process can be effectively alleviated, and its structural stability can be improved. In addition, the development of binders with sufficient adhesion to maintain good electron transfer between silicon and the current collector and achieve a stable electrode structure is also an important strategy to improve the performance of silicon-based negative electrodes. However, due to the excessive use of functional additives, the viscosity of the electrolyte increases, affecting the ion transfer rate, which greatly affects the charging performance of the battery cell, so it becomes very difficult to improve the fast charging performance. Summary of the invention
[0004] The purpose of the present invention is to provide an electrolyte for lithium-ion batteries to improve the current problems of poor stability of electrolytes in high-silicon negative electrode systems and easy expansion of batteries during cycles.
[0005] In order to achieve the above object, the present invention adopts the following technical scheme: an electrolyte, comprising a non-aqueous organic solvent, a lithium salt and an additive, wherein the additive comprises lithium difluorooxalate borate, propylene trifluorocarbonate and a fluorinated film-forming additive; the propylene trifluorocarbonate accounts for a% of the total mass of the electrolyte, the fluorinated film-forming additive accounts for b% of the total mass of the electrolyte, and the lithium difluorooxalate borate accounts for c% of the total mass of the electrolyte, wherein a, b, and c satisfy the relationship: 1<a+b+c<8, 0.2≤a / b≤60;
[0006] The fluorinated film-forming additive includes a compound shown in structural formula I:
[0007]
[0008] Wherein, R1, R2, R3, and R4 are each independently selected from one of H, F, *=C, substituted or unsubstituted C1~C12 alkyl, substituted or unsubstituted C1~C12 alkoxy, substituted or unsubstituted C2~C12 alkenyl, and substituted or unsubstituted C2~C12 alkenyloxy; or, any two of R1, R2, R3, and R4 are connected to form a ring.
[0009] Preferably, the fluorinated film-forming additive comprises at least one of the following compounds:
[0010]
[0011] Preferably, it also includes at least one of the following (1)-(3):
[0012] (1) The value range of a is 0.1 to 5;
[0013] (2) The value range of b is 0.05 to 4;
[0014] (3) The value range of c is 0.01 to 1.
[0015] Preferably, the non-aqueous organic solvent includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propyl carbonate, methyl acetate, ethyl acetate, ethyl propionate, propyl propionate, 1,3-dioxolane, tetrahydrofuran, γ-butyrolactone, 1,2-dimethoxyethane, and 2-methyltetrahydrofuran.
[0016] Preferably, the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium perchlorate, lithium tetrafluoroborate, lithium difluorophosphate, lithium trifluoromethylsulfonate and tris(trifluoromethylsulfonyl)methyllithium.
[0017] Preferably, the electrolyte further comprises at least one additive selected from the group consisting of bis(oxalatoborate), lithium difluorosulfonimide, lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium difluorophosphate, lithium difluorobis(oxalatophosphate), fluoroethylene carbonate, vinyl carbonate, 1,3-propane sultone, vinyl sulfate, methylene disulfonate, propene sultone, citraconic anhydride, ethylene glycol bis(propionitrile) ether, and hexanetrinitrile.
[0018] In addition, the present invention also provides a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator arranged between the positive electrode sheet and the negative electrode sheet, and the above-mentioned electrolyte.
[0019] Preferably, the porosity of the diaphragm is d%, wherein a, b and d satisfy the relationship: 14≤d-4*(a+b+c)≤46.
[0020] Preferably, the value range of d is 30-60.
[0021] The present invention also provides an electrical device, comprising the above-mentioned lithium-ion battery.
[0022] The beneficial effect of the present invention is that the present invention uses additives such as lithium difluorooxalate borate, trifluoropropylene carbonate and fluorinated film-forming additives in the electrolyte for synergistic matching, and controls the content ratio relationship, which can effectively improve the electrolyte solvation structure, improve the stability of the positive and negative electrodes and the battery cycle performance, and achieve the effect of improving the cycle expansion at both high and low temperatures. Among them, LiODFB can participate in film formation at the positive and negative electrodes, reduce the impedance of the positive electrode, improve the stability of CEI, and reduce the side reaction between the positive electrode and the solvent. At the same time, its film-forming product at the negative electrode can reduce the energy required for the fluorinated film-forming additive to form a film at the negative electrode. In addition, the influence of TFPC on the electrolyte solvation structure improves the solvation participation ability of DFEC, making it easy to form a LiF-rich SEI layer. DETAILED DESCRIPTION
[0023] In order to make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] According to the first aspect of the present invention, the present invention provides an electrolyte, comprising a non-aqueous organic solvent, a lithium salt and an additive, wherein the additive comprises lithium difluorooxalate borate, propylene trifluorocarbonate and a fluorinated film-forming additive; the propylene trifluorocarbonate accounts for a% of the total mass of the electrolyte, the fluorinated film-forming additive accounts for b% of the total mass of the electrolyte, and the lithium difluorooxalate borate accounts for c% of the total mass of the electrolyte, wherein a, b, and c satisfy the relationship: 1<a+b+c<8, 0.2≤a / b≤60;
[0025] The fluorinated film-forming additive includes a compound shown in structural formula I:
[0026]
[0027] Wherein, R1, R2, R3, and R4 are each independently selected from one of H, F, *=C, substituted or unsubstituted C1~C12 alkyl, substituted or unsubstituted C1~C12 alkoxy, substituted or unsubstituted C2~C12 alkenyl, and substituted or unsubstituted C2~C12 alkenyloxy; or, any two of R1, R2, R3, and R4 are connected to form a ring.
[0028] In some embodiments, the fluorinated film-forming additive includes at least one of the following compounds:
[0029]
[0030] Among them, lithium difluorooxalatoborate (LiODFB) can be used as a film-forming additive in lithium-ion battery electrolytes to improve the thermal stability of lithium-ion battery electrolytes and help form a better solid electrolyte interface (SEI) on the anode and cathode, thereby enhancing the thermal stability of the electrolyte and the electrochemical performance of the battery. Under high voltage, it can effectively inhibit the decline in electrode cycle performance. At the same time, lithium difluorooxalatoborate can form a strong, dense and conductive CEI layer at the positive electrode, thereby significantly improving the rate performance and cycle stability.
[0031] Fluorinated film-forming additives have a lower reduction potential, and they can form a stable solid electrolyte interface (SEI) layer on the anode surface of the battery, improve the interface stability inside the battery cell, reduce the growth of lithium dendrites, and thus reduce the risk of battery short circuit. Under the synergistic effect of LiODFB, the energy required for fluorinated additives to form a film can be reduced, further improving their reducibility. In addition, propylene trifluorocarbonate can maintain the conductivity of the electrolyte, ensuring that the battery has good charge and discharge performance over a wide temperature range.
[0032] Trifluoropropylene carbonate (TFPC) is an organic compound that can significantly improve the battery's cycle performance and low-temperature performance as an additive to lithium-ion battery electrolytes. Its addition can increase the flash point of the electrolyte, enhance safety, and improve the overall performance of the battery. As a bifunctional diluent cosolvent, it can participate in the interfacial chemical reaction of the electrolyte and help build a more compact and stable solid electrolyte interface (SEI) and cathode / electrolyte interface (CEI). This helps to improve the cycle stability and safety of lithium metal batteries. The use of TFPC under high-voltage conditions can effectively inhibit the oxidative decomposition of the electrolyte and improve the stability of the battery at high voltage. Studies have shown that the addition of TFPC can protect the surface of lithium metal and lithium cobalt oxide cathodes at high voltages, inhibit the occurrence of side reactions, and thus improve the battery's cycle performance.
[0033] The combined use of the above three can effectively improve the safety performance of battery electrolyte solvents.
[0034] In some embodiments, the value range of a is 0.1-5; the value range of b is 0.05-4; and the value range of c is 0.01-1.
[0035] In some embodiments, the non-aqueous organic solvent includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate, methyl acetate, ethyl acetate, ethyl propionate, propyl propionate, 1,3-dioxolane, tetrahydrofuran, γ-butyrolactone, 1,2-dimethoxyethane, and 2-methyltetrahydrofuran. Preferably, it is a mixed solvent of ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC). The mixed electrolyte solvent obtained by mixing the above three electrolyte solvents has more stable chemical properties.
[0036] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium perchlorate, lithium tetrafluoroborate, lithium difluorophosphate, lithium trifluoromethylsulfonate or tris(trifluoromethylsulfonyl)methyl lithium. Lithium hexafluorophosphate is preferred. Lithium hexafluorophosphate has a moderate ion migration number and dissociation constant in commonly used electrolyte organic solvents, ensuring the conductivity and capacity of the battery. During the first charge and discharge process of the battery, lithium hexafluorophosphate participates in the formation of a stable SEI layer, which can protect the negative electrode of the battery and prevent the continuous decomposition of the electrolyte, thereby improving the cycle stability and safety of the battery. Lithium hexafluorophosphate has good electrochemical stability, and its cathode stable voltage can reach 5.1V, which is much higher than the 4.2V required for lithium-ion batteries. It does not corrode the current collector and matches well with various positive and negative electrode materials, so it has become the most important electrolyte lithium salt used in commercial lithium-ion batteries.
[0037] In some embodiments, the electrolyte further includes at least one additive selected from the group consisting of bis(oxalatoborate), lithium difluorosulfonimide, lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium difluorophosphate, lithium difluorobis(oxalatophosphate), fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, vinyl sulfate, methylene disulfonate, propene sultone, citraconic anhydride, ethylene glycol bis(propionitrile) ether, and hexanetrinitrile.
[0038] According to a second aspect of the present invention, the present invention further provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator disposed between the positive electrode sheet and the negative electrode sheet, and the above-mentioned electrolyte.
[0039] Specifically, the porosity of the diaphragm is d%, and the relationship between a, b and d satisfies 14≤d-4*(a+b+c)≤46. The value range of d is 30-60.
[0040] Among them, the specific value of the diaphragm porosity d can be 30, 35, 40, 45, 50, 55, 60, preferably 50. The porosity of the diaphragm determines the number of ion transmission channels it can provide. Higher porosity means more ion channels, which helps to improve the ionic conductivity of the battery and the charge and discharge performance of the battery. However, too high a porosity may cause the mechanical strength of the diaphragm to decrease at high temperatures, affecting its integrity and isolation under high temperature conditions, thereby affecting the safety of the battery. When an abnormal thermal runaway occurs in the battery, the porosity and pore size of the diaphragm will affect the development speed of the thermal runaway. Appropriate porosity helps control the rate of heat release during thermal runaway.
[0041] In the present invention, the porosity of the diaphragm is combined with the electrolyte additive. The porosity of the diaphragm affects the adsorption and retention of the electrolyte by the diaphragm. A diaphragm with high porosity can adsorb more electrolyte, thereby ensuring the stability of the electrolyte and the migration of ions under long-term operation and different temperature conditions of the battery. The porosity of the diaphragm determines the number of ion transmission channels it can provide.
[0042] In some embodiments, the separator substrate includes any one of a polyolefin film, a cellulose film, a polyimide film, and a polyester film.
[0043] The present invention will be further described below by means of specific examples.
[0044] Example 1
[0045] Preparation of electrolyte:
[0046] In a glove box filled with argon, ethylene carbonate, ethyl methyl carbonate and diethyl carbonate were mixed in a mass ratio of EC:PC:DEC=1:1:3, and then 14.5wt% of lithium hexafluorophosphate (LiPF6) based on the total weight of the electrolyte was slowly added to the mixed solution, and finally 3wt% of TFPC (propylene trifluorocarbonate), 0.5wt% of LiODFB (lithium difluorooxalatoborate), 0.5wt% of compound A, 8wt% of fluoroethylene carbonate (FEC) and 1wt% of vinyl sulfate (DTD) were added based on the total weight of the electrolyte, and the mixture was stirred evenly to obtain the lithium ion battery electrolyte of Example 1.
[0047] Preparation of negative electrode:
[0048] Raw materials: hard carbon, silicon carbon (SiC), conductive agent carbon nanotube (CNT), thickener sodium carboxymethyl cellulose (CMC), binder polyaniline (PANI) and binder polyurethane (PU). A mixture of hard carbon and silicon carbon in a weight ratio of hard carbon: silicon carbon = 75:25 is used as the negative electrode active material, and each substance is mixed in a weight ratio of negative electrode active material: CNT: CMC: PANI: PU = 97.6: 0.5: 0.7: 0.7: 0.5, and deionized water is added to mix evenly to prepare a negative electrode slurry; the negative electrode slurry is coated on the current collector copper foil, dried at 85°C and cold pressed, and then trimmed, cut, and striped, and dried at 85°C vacuum for 12 hours to obtain a lithium ion battery negative electrode sheet. The hard carbon gram capacity used is 380mAh / g, the silicon carbon negative electrode gram capacity is 1810mAh / g, and the total gram capacity of the negative electrode sheet is 737.5mAh / g.
[0049] Preparation of positive electrode:
[0050] Raw materials: cathode active material lithium cobalt oxide LiCoO2, conductive agent Super P, binder polyvinylidene fluoride PVDF. After mixing the materials in a weight ratio of LiCoO2:Super P:PVDF=97.5:1:1.5, add them to N-methylpyrrolidone (NMP), mix them evenly to prepare the positive electrode slurry for lithium-ion batteries; coat the positive electrode slurry on the current collector aluminum foil, dry it at 85°C, cold press it, trim it, cut it into pieces, and divide it into strips, dry it at 85°C under vacuum for 4 hours, weld the tabs, and prepare the positive electrode sheet for lithium-ion batteries.
[0051] Preparation of the battery:
[0052] The positive electrode sheet, PE separator (wet process, Enjie), and negative electrode sheet prepared above are stacked in order, with the separator placed between the positive and negative electrode sheets, and wound to obtain a bare battery cell; the bare battery cell is placed in an aluminum-plastic film outer package, and the electrolyte prepared above is injected into the dried battery, and the battery is packaged, allowed to stand, formed, shaped, and divided to complete the preparation of the lithium-ion soft-pack battery.
[0053] Examples 2 to 9 and Comparative Examples 1 to 9 are different from Example 1 in terms of the additives added to the electrolyte and / or the porosity of the separator, as shown in Table 1. Other details are the same as Example 1 and will not be described again.
[0054] Table 1
[0055]
[0056]
[0057] The following performance tests were performed on the batteries prepared in the examples and comparative examples:
[0058] (1) High temperature cycle performance test: At 45°C, the divided battery is charged to 4.45V at 0.7C constant current and constant voltage, with a cut-off current of 0.05C, and then discharged to 3.0V at 0.5C constant current. After 500 cycles of charge and discharge, the capacity retention rate at the 500th week is calculated. The calculation formula is as follows:
[0059] The 500th cycle capacity retention rate (%) = (500th cycle discharge capacity / first cycle discharge capacity) × 100%.
[0060] (2) 60℃ 14d high temperature storage test: The battery was placed at room temperature and charged and discharged once at 0.5C (4.45V-3.0V), and the discharge capacity C0 of the battery before storage was recorded. The battery was then charged to 4.45V at constant current and constant voltage. The thickness d1 of the battery before high temperature storage was tested using a PPG battery thickness gauge (500g). The battery was placed in a 60℃ constant temperature box and stored for 14 days. After the storage was completed, the battery was taken out and the thermal thickness d2 of the battery after storage was tested. The thickness expansion rate of the battery after 60℃ storage for 14 days was calculated. After the battery was cooled at room temperature for 24h, the battery was again discharged to 3.0V at 0.5C at constant current and then charged to 4.45V at 0.5C at constant current and constant voltage. The discharge capacity C1 and charge capacity C2 of the battery after storage were recorded. The capacity remaining rate and recovery rate of the battery after 60℃ storage for 14 days were calculated using the following formula:
[0061] Thickness expansion ratio after storage at 60°C for 14 days = (d2-d1) / d1*100%;
[0062] After 14 days of storage at 60°C, capacity retention rate = C1 / C0*100%;
[0063] After storage at 60°C for 14 days, the capacity recovery rate = C2 / C0*100%.
[0064] (3) Thermal shock performance: At 25°C, discharge to 3.0V at a given current of 0.2C; leave for 5 minutes; charge to 4.45V at a charging current of 0.2C. When the cell voltage reaches 4.45V, change to 4.45V constant voltage charging until the charging current is less than or equal to the given cut-off current of 0.05C; after leaving for 1 hour, put the cell into an oven, and increase the oven temperature to 135±2°C at a rate of 5±2°C / min, and keep it for 30 minutes before stopping. The judgment standard is that the cell does not catch fire or explode.
[0065] The battery performance test results of Examples 1-9 and Comparative Examples 1-9 are shown in Table 2.
[0066] Table 2
[0067]
[0068]
[0069] According to the test results in the above table, the combination of LiODFB, fluorinated film-forming additives and TFPC in the embodiments of the present invention, and satisfying the following conditions: 1<a+b+c<8, 0.2≤a / b≤60, 14≤d-4*(a+b+c)≤46, can effectively improve the stability of the electrolyte system and the positive and negative electrodes, thereby improving the battery cycle performance, thereby effectively improving the problems of cyclic expansion and poor high temperature stability of the silicon system.
[0070] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. An electrolyte, characterized in that: Including non-aqueous organic solvent, lithium salt and additives, The additives include lithium difluorooxalate borate, propylene trifluorocarbonate and a fluorinated film-forming additive; the propylene trifluorocarbonate accounts for a% of the total mass of the electrolyte, the fluorinated film-forming additive accounts for b% of the total mass of the electrolyte, and the lithium difluorooxalate borate accounts for c% of the total mass of the electrolyte, wherein a, b, and c satisfy the relationship: 1<a+b+c<8, 0.2≤a / b≤60; The fluorinated film-forming additive includes a compound shown in structural formula I: Wherein, R1, R2, R3, and R4 are each independently selected from one of H, F, *=C, substituted or unsubstituted C1~C12 alkyl, substituted or unsubstituted C1~C12 alkoxy, substituted or unsubstituted C2~C12 alkenyl, and substituted or unsubstituted C2~C12 alkenyloxy; or, any two of R1, R2, R3, and R4 are connected to form a ring.
2. The electrolyte according to claim 1, characterized in that The fluorinated film-forming additive comprises at least one of the following compounds:
3. The electrolyte according to claim 1, characterized in that Also includes at least one of the following (1)-(3): (1) The value range of a is 0.1 to 5; (2) The value range of b is 0.05 to 4; (3) The value range of c is 0.01 to 1.
4. The electrolyte according to claim 1, characterized in that The non-aqueous organic solvent includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propyl ethyl carbonate, methyl acetate, ethyl acetate, ethyl propionate, propyl propionate, 1,3-dioxolane, tetrahydrofuran, γ-butyrolactone, 1,2-dimethoxyethane, and 2-methyltetrahydrofuran.
5. The electrolyte according to claim 1, characterized in that The lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium perchlorate, lithium tetrafluoroborate, lithium difluorophosphate, lithium trifluoromethylsulfonate and tris(trifluoromethylsulfonyl)methyllithium.
6. The electrolyte according to claim 1, characterized in that The electrolyte also includes at least one additive selected from the group consisting of bis(oxalato)borate, lithium difluorosulfonimide, lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium difluorophosphate, lithium difluorobis(oxalato)phosphate, fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, vinyl sulfate, methylene disulfonate, propene sultone, citraconic anhydride, ethylene glycol bis(propionitrile) ether, and hexanetrinitrile.
7. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, a separator arranged between the positive electrode sheet and the negative electrode sheet, and the electrolyte according to any one of claims 1 to 6.
8. The lithium-ion battery according to claim 7, characterized in that: The porosity of the diaphragm is d%, wherein a, b and d satisfy: 14≤d-4*(a+b+c)≤46.
9. The lithium-ion battery according to claim 8, characterized in that: The value range of d is 30-60.
10. An electrical device, characterized in that: Comprising a lithium ion battery as claimed in any one of claims 7 to 9.
Citation Information
Patent Citations
High-temperature lithium battery electrolyte
CN107230804A
Lithium battery electrolyte and lithium ion battery
CN110994030A
High-voltage electrolyte
CN117790892A
Electrolytic solution for non-aqueous secondary battery, and non-aqueous secondary battery using the same
JP2022076996A